The relationship level of community's knowledge and attitude toward the use of antibiotics in Gandaria, South Jakarta - Teodhora, Teodhora; Maliawati, Eka Putri (Universitas Ahmad Dahlan, 2023)
Antibiotics will be beneficial and have the anticipated therapeutic effect if prescribed and administered as instructed. The purpose of this study was to evaluate community attitudes and knowledge levels regarding the use of antibiotics, as well as the relationship between these two variables. The sample size for this descriptive-analytic study was 95 respondents, and a cross-sectional design was used. The sampling technique utilized was purposeful sampling. Women made up the bulk of responses (65.3%), and their age range was 36 to 45 (44.2%). The latest educational levels indicated were high school (61.1%), antibiotic use in the past or present (100%), and housewife (38.1%). The respondent received scores of 62.1% for